Molecular characterisation of coding regions of HIF-1a gene in Vechur cattle by cDNA sequencing. Issue 12 (December 2022) - Ramya, P.R.; Beena, V.; Radhika, G.; Shynu, M.; Jayavardhanan, K.K.
Abstract: Hypoxia-inducible factor (HIF)-1α is a transcription factor stabilized by hypoxia by inducing or suppressing the homeostatic regulatory gene expression, enabling tissues and cells to survive despite fluctuations in environmental circumstances. As the name implies, hypoxia-inducible factor-1 is secreted not only as a cellular response to hypoxia but also in heat stress and oxidative stress. The goal of this work was to determine the molecular characterisation of the HIF-1α gene coding region as well as the differences in HIF-1αprotein primary structure between Vechur cattle and other cattle breeds in the online databases. Total RNA was isolated from blood samples of 6 Vechur cattle using the trizol reagent method, and full-length c sequences of the HIF-1 α gene were sequenced. The base pair length of composite HIF-1α cDNA of Vechur cattle and encoding ORFis 3956 bp and 2469 bp respectively. The 5′UTR was recognized to be 279 bp in length. The start codon was identified at nucleotide 280–282, the stop codon UGA at 2746–2748 bp and a 1208 bp 3′UTR which included a poly-A tail of 27 adenine residues. In a comparative analysis of the cDNA, point transitions causing guanine to adenine (G > A) changes at 1211th and 2699th positions were noticed as a heterozygous condition in the whole 3956 bp sequence. These two SNVs in the coding regions were responsible for two amino acid changes in the deduced 823 amino acid sequence. Since the predicted amino acid arginine had been replaced with lysine at 311th and 807th positions, it showed 99.76 percent sequence identity with Bos taurus . The phylogenetic tree revealed that the HIF-1α protein of Vechur cattle had a lesser evolutionary distance from the same gene of related species emphasising the highly conserved nature of this particular protein. This structural variation observed in the present study should be evaluated on a larger population to assess its functional relevance for thermo-tolerance. Abstract : Hypoxia-inducible factor; Molecular characterisation; Point transitions; Phylogenic tree; Single nucleotide variations (SNVs).